2006
DOI: 10.1007/s10483-006-0512-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamical bifurcation and chaotic motion of shallow conical lattice shell

Abstract: The nonlinear dynamical equations of axle symmetry are established by the method of quasi-shells for three-dimensional shallow conical single-layer lattice shells. The compatible equations are given in geometrical nonlinear range. A nonlinear differential equation containing the second and the third order nonlinear items is derived under the boundary conditions of fixed and clamped edges by the method of Galerkin. The problem of bifurcation is discussed by solving the Floquet exponent. In order to study chaoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Chaotic vibrations of shallow conical panels can be found in Refs. [81,178,179,205]. Krysko et al [81,178] found the Feigenbaum scenario for conical panels subjected to large harmonic excitations.…”
Section: Spherical Caps and Panels Of Other Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaotic vibrations of shallow conical panels can be found in Refs. [81,178,179,205]. Krysko et al [81,178] found the Feigenbaum scenario for conical panels subjected to large harmonic excitations.…”
Section: Spherical Caps and Panels Of Other Geometriesmentioning
confidence: 99%
“…Awrejcewicz et al [179] discussed the routes to chaos of conical panels with non homogenous thickness. Wang et al [205] used the Melinkov method to discuss the chaotic response of a conical lattice shell modeled as a single degree of freedom system.…”
Section: Spherical Caps and Panels Of Other Geometriesmentioning
confidence: 99%